Diamonds in the data. - Brooks, Michael (New Statesman, 2015)
The article focuses on how the European Organisation for Nuclear Research's (CERN) particle accelerator Large Hadron Collider (LHC) will result in technological innovations. It states that the next spin-off technology from CERN will be in data processing and the mining of data. It mentions the physics research will also push innovations in data compression and storage and comments on CERN's computer network The Grid used in LHC data processing.